Long non-coding RNA lncMGC mediates the expression of TGF-β-induced genes in renal cells via nucleosome remodelers - Kato, Mitsuo; Chen, Zhuo; Das, Sadhan; Wu, Xiwei; Wang, Jinhui; Li, Arthur; Chen, Wei; Tsark, Walter; Tunduguru, Ragadeepthi; Lanting, Linda; Wang, Mei; Moore, Roger; et al. (Frontiers in Molecular Biosciences, 2023)
Background: microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) play key roles in diabetic kidney disease (DKD). miR-379 megacluster of miRNAs and its host transcript lncMGC (lnc-megacluster) are regulated by transforming growth factor-β (TGFβ), increased in glomeruli of diabetic mice and promote features of early DKD. However, biochemical functions of lncMGC are unknown. Here we identified lncMGC-interacting proteins by in vitro-transcribed lncMGC RNA-pull down followed by mass spectrometry (MS). We also created lncMGC knockout (KO) mice by CRISPR-Cas9 editing and used primary mouse mesangial cells (MMC) from the KO mice to examine the effects of lncMGC on gene expression related to DKD, changes in promoter histone modifications and chromatin remodeling. Methods: In vitro transcribed lncMGC RNA was mixed with lysates from HK2 cells (human kidney cell line). lncMGC interacting proteins were identified by MS. Candidate proteins were confirmed by RNA immunoprecipitation (RIP) followed by qPCR. Cas9 and guide RNAs were injected into mouse eggs to create lncMGC-KO mice. Wild type (WT) and lncMGC-KO MMC were treated with TGF-β and RNA expression (by RNA-seq and qPCR) and histone modifications (by chromatin immunoprecipitation) and chromatin remodeling/open chromatin (by Assay for Transposase-Accessible Chromatin, ATAC-seq) were examined. Results: Several nucleosome remodeling factors including SMARCA5 and SMARCC2 were identified as lncMGC interacting proteins by MS, and confirmed by RIP-qPCR. MMC from lncMGC-KO mice showed no basal or TGF-β-induced expression of lncMGC. Enrichment of histone H3K27 acetylation and SMARCA5 at the lncMGC promoter was increased in TGF-β-treated WT MMC but significantly reduced in lncMGC-KO MMC. ATAC peaks at the lncMGC promoter region as well as many other DKD-related loci including Col4a3 and Col4a4 were significantly lower in lncMGC-KO MMC than WT MMC in TGF-β-treated condition. Zinc-Finger (ZF), ARID, and SMAD motifs were enriched in ATAC-peaks. ZF and ARID sites were also found in the lncMGC gene. Conclusion: lncMGC RNA interacts with several nucleosome remodeling factors to promote chromatin relaxation and enhance the expression of lncMGC itself and other genes including pro-fibrotic genes. lncMGC/nucleosome remodeler complex promotes site-specific chromatin accessibility to enhance DKD-related genes in target kidney cells.